Spherical zeolite production method
Incorporating surfactants in the zeolite synthesis gel produces spherical zeolite with low thermal expansion, addressing viscosity and thermal cycle resistance issues, enhancing the injectability and performance of resin compositions as underfill materials.
Patent Information
- Application Number
- JP2023108459
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Liquid sealants using inorganic fillers like silica do not have a sufficiently low coefficient of thermal expansion, and compositions containing zeolite tend to have high viscosity, making it difficult to achieve good injectability and thermal cycle resistance.
A method for producing spherical zeolite by incorporating a surfactant in the zeolite synthetic raw material gel, specifically using ionic surfactants like cationic or anionic surfactants, to facilitate the production of zeolite with a low coefficient of thermal expansion and low viscosity.
The method enables the production of spherical zeolite with high sphericity and low thermal expansion, resulting in a resin composition with improved injectability and thermal cycle resistance, suitable for use as an underfill material.
Smart Images

Figure 2025007209000002 
Figure 2025007209000003 
Figure 2025007209000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing spherical zeolite. [Background technology]
[0002] Liquid sealants used as underfill materials are required to have excellent injectability, adhesion, curing properties, storage stability, etc., and to be free of voids. In addition, the parts sealed with the liquid sealant are required to have excellent moisture resistance, thermal cycle resistance, reflow resistance, crack resistance, warping resistance, etc. In order to satisfy the above requirements, liquid sealants mainly composed of epoxy resins are widely used as underfill materials.
[0003] Furthermore, in order to improve the moisture resistance and thermal cycle resistance, particularly the thermal cycle resistance, of the area sealed with the liquid sealant, it is known that a filler made of an inorganic substance such as silica filler (hereinafter referred to as "inorganic filler") can be used in the liquid sealant to control the difference in thermal expansion coefficient between the substrate made of an organic material such as epoxy resin and the semiconductor element and to reinforce the bump electrodes (Patent Document 1). Specifically, Patent Document 1 discloses an underfill material for flip-chip semiconductor devices, which comprises (A) an epoxy resin, (B) a polyfunctional aliphatic epoxy having an average molecular weight of 200 or more and being liquid at room temperature, (C) a basic curing agent that is solid at 100°C, and (D) an inorganic filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-56070 A Summary of the Invention [Problem to be solved by the invention]
[0005] Liquid sealants using inorganic fillers such as silica fillers do not have a sufficiently low thermal expansion coefficient, and there is a demand for a further reduction in the thermal expansion coefficient from the viewpoint of thermal cycle resistance, etc. In addition, zeolite is known as an inorganic filler with a low thermal expansion coefficient, but liquid compositions containing zeolite tend to have high viscosity, which reduces the injectability when used as an underfill material, making it difficult to obtain a liquid sealant with good injectability while reducing the thermal expansion coefficient of the cured product.
[0006] On the other hand, for underfill materials using zeolite as an inorganic material, it is important that the zeolite is spherical, and therefore a method for efficiently producing spherical zeolite is important. Therefore, an object of the present invention is to provide an efficient method for producing spherical zeolite suitable for obtaining a composition having a low viscosity and a low thermal expansion coefficient after curing. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above problems, the present inventors have found that by including a specific surfactant in the raw material gel for zeolite synthesis, it is possible to effectively produce spherical zeolite. The present invention has been completed based on this finding.
[0008] That is, the present invention relates to the following. [1] A method for producing spherical zeolite having d6r as CBU, characterized in that a surfactant is contained in the zeolite synthesis raw material gel. [2] A method for producing a spherical zeolite according to the above [1], wherein the zeolite has a structure of an oxygen ring with 8 or less members. [3] A method for producing a spherical zeolite according to the above [1] or [2], wherein the proportion of particles having a circularity of 0.8 or more in the zeolite is 90% or more. [4] The method for producing a spherical zeolite according to any one of the above [1] to [3], wherein the zeolite is a CHA-type zeolite. [5] The method for producing a spherical zeolite according to any one of the above [1] to [4], wherein the surfactant is an ionic surfactant. [6] The method for producing spherical zeolite described in [5] above, wherein the ionic surfactant is an anionic surfactant or a cationic surfactant. [7] A method for producing a spherical zeolite according to any one of the above [1] to [6], wherein the synthesis raw gel contains a silicon atom raw material, an aluminum atom raw material, a surfactant and water, and the method comprises a step of hydrothermally synthesizing the synthesis raw gel. [8] The method for producing spherical zeolite according to the above [7], wherein the synthesis raw material gel further contains an organic structure-directing agent. [9] A method for producing a spherical zeolite according to the above [7] or [8], further comprising a drying step and a calcination step. Effect of the Invention
[0009] According to the present invention, there can be provided a method for producing spherical zeolite suitable for obtaining a composition having a low viscosity and a low thermal expansion coefficient after curing. [Brief description of the drawings]
[0010] [Figure 1] 1 is an XRD chart of powders of Example 1 and Comparative Example 1. [Diagram 2] 1 is a SEM image (magnification 2000 times) of the zeolite of Example 1. [Diagram 3] 1 is a SEM image (magnification: 2000 times) of the zeolite of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described in detail. Note that the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the contents thereof as long as it does not depart from the gist of the present invention.
[0012] The manufacturing method of the present invention is a method for manufacturing a spherical zeolite having d6r as a CBU, and is characterized in that a surfactant is contained in the synthesis raw gel of the zeolite. By containing a surfactant in the synthesis raw gel, the spherical zeolite can be efficiently manufactured.
[0013] <Surfactant> As the surfactant, cationic surfactants, anionic surfactants, nonionic surfactants, amphoteric surfactants, etc. can be used alone or in combination. Among these, as the surfactant, ionic surfactants are preferred, and specifically, cationic surfactants and anionic surfactants are preferred.
[0014] (cationic surfactant) Examples of the cationic surfactant include quaternary ammonium salts and alkylamine salts. The quaternary ammonium salt includes ammonium salts represented by the following general formula (1). [R 1 n (CH3) 4-n N] + [X] - (1) (In the formula, R 1 represents a long-chain alkyl group, n is an integer of 1 to 3, and X represents a halogen atom or a hydroxyl group. In particular, a halide or hydroxide of a quaternary long-chain alkyl trimethylammonium having a substitution number n of 1 is preferred because it allows efficient production of spherical zeolite. 1 The carbon number is preferably 8 to 24, and particularly preferably 8 to 17. When the carbon number is 8 or more, the function as a surfactant can be sufficiently exhibited, and when the carbon number is 24 or less, the surfactant is soluble in water and easy to handle. As the halogen atom of X, a chlorine atom and a bromine atom are preferred because they are easily available as industrial products. In the general formula (1), X is preferably a hydroxyl group because the subsequent washing treatment for removing Na is easy.
[0015] Specific examples of the quaternary long-chain alkyl trimethyl ammonium salt include octyl trimethyl ammonium chloride, octyl trimethyl ammonium bromide, octyl trimethyl ammonium hydroxide, decyl trimethyl ammonium chloride, decyl trimethyl ammonium bromide, decyl trimethyl ammonium hydroxide, dodecyl trimethyl ammonium chloride, dodecyl trimethyl ammonium bromide, dodecyl trimethyl ammonium hydroxide, hexadecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium bromide (CTAB; cetyl trimethyl ammonium bromide), hexadecyl trimethyl ammonium hydroxide, octadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium bromide, and octadecyl trimethyl ammonium hydroxide. These quaternary long-chain alkyl trimethyl ammonium salts may be used alone or in combination of two or more. Among these, hexadecyltrimethylammonium bromide (CTAB; cetyltrimethylammonium bromide) is particularly preferred since it allows efficient production of spherical zeolite.
[0016] The alkylamine salt includes an alkylamine salt represented by the following general formula (2). [R 2 NH2〕 + [X] - (2) (In the formula, R 2 represents a long-chain alkyl group, and X represents a halogen atom or a hydroxyl group. In the general formula (2), the long-chain alkyl group R 2 The carbon number is preferably 8 to 24, and particularly preferably 8 to 17. When the carbon number is 8 or more, the function as a surfactant can be sufficiently exhibited, and when the carbon number is 24 or less, the surfactant is soluble in water and easy to handle.
[0017] In the present invention, the above-mentioned quaternary long-chain alkyl trimethyl ammonium salts are preferred because they have a higher basicity than alkyl amine salts and therefore have excellent reactivity. The content of the cationic surfactant, expressed as a molar ratio (SiO2 / cationic surfactant) to the silicon atom raw material (oxide equivalent) in the synthetic gel raw material described in detail later, is preferably 100 to 1000, more preferably 300 to 700. By using within this range, spherical zeolite with high sphericity can be obtained.
[0018] (Anionic surfactants) Examples of anionic surfactants include sulfonic acid surfactants, sulfate ester surfactants, carboxylic acid surfactants, and phosphate ester surfactants.
[0019] ((Sulfonic acid type surfactant)) Examples of sulfonic acid surfactants include α-sulfo fatty acid methyl ester salts (CH3(CH2)) such as sodium methyl α-sulfomyristate and sodium methyl α-sulfostearate. s Examples of the sulfonate include α-sulfofatty acid ester salts such as CH(SO3Na)COCH3, where s is 8 to 20); alkylbenzenesulfonates such as sodium p-toluenesulfonate, sodium cumenesulfonate, sodium octylbenzenesulfonate, and sodium dodecylbenzenesulfonate; alkanesulfonates such as sodium hexylsulfonate, sodium octylsulfonate, sodium decylsulfonate, sodium dodecylsulfonate, sodium tetradecylsulfonate, sodium hexadecylsulfonate, and sodium stearylsulfonate; and α-olefinsulfonates having 8 to 26 carbon atoms.
[0020] ((Sulfate ester type surfactant)) Examples of sulfate ester surfactants include R surfactants such as sodium hexyl sulfate, sodium octyl sulfate, sodium decyl sulfate, sodium dodecyl sulfate, sodium tetradecyl sulfate, sodium hexadecyl sulfate, sodium stearyl sulfate, and sodium laureth sulfate. 1 -OSO3Na(R 1= saturated hydrocarbon group having 8 to 18 carbon atoms or unsaturated hydrocarbon group having one double bond); polyoxyethylene alkyl ether sulfate; fatty acid monoglyceride sulfate such as sodium lauric acid monoglyceride sulfate; R 2 CONHCH2CH2OSO3Na(R 2 = fatty acid having 7 to 20 carbon atoms); and the like.
[0021] ((Carboxylic acid type surfactant)) Examples of carboxylic acid type surfactants include sodium octanoate, sodium decanoate, sodium laurate, sodium oleate, sodium myristate, sodium palmitate, sodium stearate, potassium laurate, potassium oleate, perfluorooctanoic acid, perfluorononanoic acid, alkyloyl sarcosines such as sodium N-lauroyl sarcosine; sodium cocoyl glutamate ((HOCCH2CH2CH(NHCOR 3 )COONa), where R 3 = alkyl group having 11 to 17 carbon atoms).
[0022] ((Phosphate ester type surfactant)) Examples of phosphate ester surfactants include lauryl phosphate, sodium monoalkyl phosphates such as sodium lauryl phosphate, sodium hexyl phosphate, sodium octyl phosphate, sodium decyl phosphate, sodium dodecyl phosphate, sodium tetradecyl phosphate, and sodium hexadecyl phosphate, potassium monoalkyl phosphates such as potassium lauryl phosphate, potassium hexyl phosphate, potassium octyl phosphate, potassium decyl phosphate, potassium dodecyl phosphate, potassium tetradecyl phosphate, and potassium hexadecyl phosphate, polyoxyethylene alkyl ether phosphate, sodium polyoxyethylene lauryl ether phosphate, and sodium polyoxyethylene tridecyl ether phosphate, etc. The alkyl group of the anionic amphiphilic substance described above preferably has 8 to 20 carbon atoms.
[0023] Among these anionic surfactants, carboxylic acid surfactants are preferred from the viewpoint of efficient production of spherical zeolite, and sodium oleate is particularly preferred. The content of the anionic surfactant, expressed as a molar ratio (SiO2 / anionic surfactant) to the silicon atom raw material (oxide equivalent) in the synthetic gel raw material described in detail later, is preferably 1 to 100, more preferably 30 to 70. By using within this range, spherical zeolite with high sphericity can be obtained.
[0024] <Synthetic raw material gel> The synthesis raw material gel for producing the spherical zeolite of the present invention contains a silicon atom raw material, an aluminum atom raw material, a surfactant, and water. The surfactant is as described above. The raw materials constituting the synthesis raw material gel will be described in detail below.
[0025] (Silicon atom source) The silicon atom source used in the present invention is not particularly limited, and various known substances can be used. Specifically, amorphous silica such as colloidal silica, amorphous silica, fumed silica, and sodium silicate, silane oligomers obtained by hydrolysis and polymerization of alkoxysilanes such as trimethylethoxysilane and tetraethylorthosilicate, silica sol, aluminosilicate gel, and zeolite can be used. These may be used alone or in any combination and ratio of two or more. Among these, amorphous silica is preferred because it is easily dissolved in water and is inexpensive. From the viewpoints of being easily mixed uniformly with other raw materials and being easily dissolved in water, colloidal silica, silane oligomer, and aluminosilicate gel are preferred, and colloidal silica is particularly preferred.
[0026] (Aluminum atom source) The aluminum atom source is preferably a compound that is easily soluble in water, and is also preferably a compound that is easily miscible with the silicon atom source and that is easily soluble so as to provide a Si / Al ratio suitable for zeolite crystallization during the aging and hydrothermal synthesis steps. From the above viewpoints, preferred aluminum atom raw materials are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, aluminum hydroxide having a bayerite structure, aluminum nitrate, aluminum sulfate, aluminum oxide, sodium aluminate, boehmite, pseudo-boehmite, aluminum alkoxide, etc. These may be used alone or in any combination of two or more kinds in any ratio. Among these, particularly preferred are amorphous aluminum hydroxide, aluminum hydroxide having a gibbsite structure, and aluminum hydroxide having a bayerite structure. The aluminum atom raw material is preferably amorphous, and among the above, amorphous aluminum hydroxide is particularly preferred.
[0027] (water) When using a seed zeolite described later, the amount of water used is usually 5 or more, preferably 7 or more, more preferably 9 or more, and even more preferably 10 or more in terms of the molar ratio to silicon (Si) contained in the raw material composition other than the seed zeolite, from the viewpoint of facilitating crystal formation. By setting the amount of water within this range, crystal formation is facilitated. In addition, by hydrothermally synthesizing zeolite under conditions in which the amount of water is increased and the raw material concentration is diluted, it is easy to produce zeolite with a large particle size. In terms of facilitating the cost reduction effect for waste liquid treatment, the molar ratio to silicon (Si) is usually 50 or less, preferably 40 or less, more preferably 30 or less, and even more preferably 25 or less.
[0028] (Organic structure directing agent) The synthesis raw material gel of the present invention preferably contains an organic structure-directing agent in addition to the silicon atom raw material, the aluminum atom raw material, the surfactant, and water. As the organic structure directing agent, various known substances such as tetraethylammonium hydroxide (TEAOH) and tetrapropylammonium hydroxide (TPAOH) can be used. Among these, N,N,N-trimethyl-1-adamantaammonium hydroxide (TMAdaOH) is preferred. The amount of the organic structure directing agent used is, in terms of molar ratio to silicon (Si) contained in the synthesis raw material gel, usually 0.01 or more, preferably 0.02 or more, more preferably 0.03 or more, particularly preferably 0.04 or more, and most preferably 0.05 or more. On the other hand, it is usually 1 or less, preferably 0.6 or less, more preferably 0.55 or less, and even more preferably 0.5 or less. By using within this range, it is thought that high-purity spherical zeolite with few by-products is easily grown.
[0029] (Alkali metal atom source) Zeolite may be produced using an alkali metal atom raw material. When using an alkali metal atom raw material, the alkali metal atom is not particularly limited, and any known alkali metal atom used in the synthesis of zeolite may be used, but at least one alkali metal selected from the group consisting of lithium, sodium, potassium, rubidium, and cesium is preferred. Note that multiple types of alkali metal atoms may be used.
[0030] (Seed zeolite) In the method for producing zeolite, a seed zeolite may be used. When a seed zeolite is used, one type may be used alone, or two or more types may be used in any combination and ratio.
[0031] <Zeolite> In the production method of the present invention, the target zeolite is a spherical zeolite having d6r as the CBU.
[0032] (Zeolite structure) Zeolite is a compound that contains silicon or aluminum and oxygen and has a TO4 unit (T element is an element other than oxygen that constitutes the framework) as a basic unit. Specific examples of zeolite include crystalline porous aluminosilicates, crystalline porous aluminophosphates (ALPOs), and crystalline porous silicoaluminophosphates (SAPOs), but the zeolite according to the embodiment of the present invention is an aluminosilicate. Zeolite is made up of structural units called Composite Building Units (hereinafter referred to as "CBUs"), which are made up of several (several to several tens) TO4 units connected together. This gives the zeolite regular channels (tubular pores) and cavities. The CBU and the crystal structure of zeolite, which will be described later, can be shown by the code that specifies the structure of zeolite, as defined by the International Zeolite Association (IZA). The structure of zeolite can be identified using the Zeolite Structure Database 2018 Edition (http: / / www.iza-structure.org / databases / ) based on the X-ray diffraction pattern obtained by an X-ray structure analyzer (e.g., BRUKER's tabletop X-ray diffractometer D2PHASER).
[0033] (Zeolite framework) The framework of the zeolite according to the present invention has d6r as a CBU. By having d6r, it is easy to obtain a resin composite material having a low thermal expansion coefficient, which will be described in detail later. As the CBU, examples of zeolites having d6r include AEI, AFT, AFV, AFX, AVL, CHA, EAB, EMT, ERI, FAU, GME, JSR, KFI, LEV, LTL, LTN, MOZ, MSO, MWW, OFF, SAS, SAT, SAV, SBS, SBT, SFW, SSF, SZR, TSC, and zeolites having a -WEN type structure. Among these, from the viewpoint of easy control of particle size, zeolites having an 8-membered oxygen ring or less structure are particularly preferred. Zeolites having an 8-membered oxygen ring or less structure include zeolites having AEI, AFT, AFX, CHA, ERI, KFI, SAT, SAV, SFW, and TSC type structures. Among these, zeolites having AEI, AFX, CHA, and ERI type structures are particularly preferred, and zeolites having CHA type structures are most preferred, since the structure is stable even when the shape is controlled. In this specification, the structure having an 8-membered oxygen ring means a structure in which the number of oxygen elements is 8 when the number of oxygen elements is the largest among the pores composed of oxygen and T elements (elements other than oxygen that constitute the framework) that form the zeolite framework.
[0034] (Average thermal expansion coefficient of zeolite) The average thermal expansion coefficient of the zeolite according to the present invention is preferably low because it is easy to reduce the average thermal expansion coefficient of the liquid composition and the resin composite material described later with a small amount of zeolite. In addition, it is also preferable that the amount of zeolite is small because various physical properties of the resin are unlikely to change due to the addition of zeolite. In particular, it is preferable that the average thermal expansion coefficient is low because it can suppress the increase in viscosity of the liquid composition described later. Specifically, the average thermal expansion coefficient of the zeolite is usually less than 0 ppm / K, preferably -2 ppm / K or less, more preferably -3 ppm / K or less, even more preferably -5 ppm / K or less, particularly preferably -6 ppm / K or less, and most preferably -8 ppm / K or less.
[0035] On the other hand, considering that the zeolite is used as a liquid composition and a resin composite material containing zeolite and a resin, described later, the difference between the average thermal expansion coefficient of the zeolite and the average thermal expansion coefficient of the resin is small, and it is preferable that the average thermal expansion coefficient of the zeolite is high in that the zeolite and the resin are not easily peeled off. Therefore, the average thermal expansion coefficient of the zeolite is usually -1000 ppm / K or more, preferably -900 ppm / K or more, more preferably -800 ppm / K or more, even more preferably -700 ppm / K or more, particularly preferably -500 ppm / K or more, and especially preferably -300 ppm / K or more. And, in particular, when used for applications in contact with other materials such as sealing materials and substrates, it is preferable that the average thermal expansion coefficient is high, specifically, preferably -100 ppm / K or more, more preferably -50 ppm / K or more, even more preferably -40 ppm / K or more, particularly preferably -30 ppm / K or more, especially preferably -25 ppm / K or more, and most preferably -20 ppm / K or more. The average thermal expansion coefficient of zeolite can be measured by calculating the lattice constant using the X-ray diffractometer "D8ADVANCE" manufactured by BRUKER and the X-ray diffraction analysis software "JADE". In order to eliminate the influence of moisture desorption, the zeolite is usually measured in a dry state. The average thermal expansion coefficient of zeolite is usually measured in the range of 50 to 100°C. That is, it is a numerical value that represents the displacement of the lattice constant per 1°C from the average lattice constant at 50°C and the average lattice constant at 100°C when the temperature of the zeolite is raised. Here, the average lattice constant at each temperature is the average value of the lattice constants of the a-axis, b-axis, and c-axis. The average thermal expansion coefficient is measured by gradually raising the temperature after waiting until the lattice constant stabilizes.
[0036] Generally, the thermal expansion coefficient of resins is large in high temperature ranges. Therefore, it is preferable that the average thermal expansion coefficient of zeolite is low, especially when the temperature is raised to a high temperature range. Specifically, the average thermal expansion coefficient (high temperature range) in the range of 50 to 350°C is preferably -9.5 ppm / K or less, more preferably -10.0 ppm / K or less, and even more preferably -12.5 ppm / K or less. Here, the average thermal expansion coefficient (high temperature range) of zeolite is a numerical value representing the displacement of the lattice constant per 1°C from the average lattice constant at 50°C and the average lattice constant at 350°C when the zeolite is heated.
[0037] (Zeolite shape) It is important that the shape of the zeolite according to the present invention is spherical, since this makes it easy to incorporate the zeolite into a composition while suppressing an increase in the viscosity of the composition. Specifically, it is preferable that the proportion of particles having a certain degree of sphericity or roundness shown below is high.
[0038] <<Sphericity>> The sphericity of the zeolite is preferably high, and the ratio of the number of particles with high sphericity to the total number of particles is preferably high. Specifically, the ratio of the number of particles with a sphericity of 0.6 or more is preferably 90% or more, more preferably 93% or more, and most preferably 95% or more. The sphericity of a cube, which is common in normal zeolites, is 0.58. In the present application, the "sphericity" of each particle is obtained by a scanning electron microscope (SEM), and the "ratio of the number of particles with a sphericity of 0.6 or more" is obtained by determining the sphericity of 100 or more particles. In this specification, "sphericity" is defined as "the ratio of the minimum diameter of a particle to the maximum diameter."
[0039] <<Circularity>> The circularity of the zeolite is preferably high, and the ratio of the number of particles with high circularity to the total number of particles is preferably high. Specifically, the ratio of the number of particles with a circularity of 0.8 or more is preferably 90% or more, more preferably 93% or more, and most preferably 95% or more. The circularity of a cube, which is common in normal zeolites, is 0.79. In the present application, the "circularity" of each particle is obtained by a scanning electron microscope (SEM), and the "ratio of the number of particles with a circularity of 0.8 or more" is obtained by determining the circularity of 100 or more particles. In this specification, the "roundness" is defined as a value calculated by the following formula (3). Circularity = 4π × (S / L 2 ) Formula (3) In formula (3), S is the area and L is the perimeter. They can be determined by observation with a scanning electron microscope (SEM), and in this case, S is the projected area.
[0040] <<Aspect ratio>> The higher the aspect ratio of the zeolite, the more preferable it is, and the greater the proportion of particles with a high aspect ratio to the total particles. Specifically, the proportion of particles with an aspect ratio of 0.8 or more is preferably 70% or more, more preferably 73% or more, and most preferably 75% or more. There is no particular upper limit to the aspect ratio, and the aspect ratio may be 1 or less. In the present application, the "aspect ratio" of each particle is obtained by a scanning electron microscope (SEM), and the "proportion of particles with an aspect ratio of 0.8 or more" is obtained by determining the aspect ratios of 100 or more particles. In this specification, the "aspect ratio" is defined as the ratio of the minor axis length to the major axis length of an elliptical particle. The major axis length and minor axis length can be determined by observation with a scanning electron microscope (SEM).
[0041] (Zeolite framework density) The framework density of the zeolite to be produced in the present invention is not particularly limited as long as the effects of the present invention are not impaired. The framework density of the zeolite is preferably low in that the structural vibration of the zeolite is likely to occur and the average thermal expansion coefficient is likely to be low. Therefore, the framework density of the zeolite is preferably 17.0T / 1000Å or less. 3 Less than or equal to 16.0T / 1000Å, more preferably 3 The following is the result. On the other hand, it is preferable that the framework density of the zeolite is high in order to increase the structural stability of the zeolite. The framework density of the zeolite is preferably 12.0T / 1000Å. 3 More preferably, 13.0T / 1000Å or more 3 More preferably, 14.0T / 1000Å or more 3 When the framework density is within the above range, the zeolite can be used as a stable filler. The framework density refers to the number of T atoms present per unit volume of zeolite, and is a value determined by the structure of the zeolite. In this specification, the numerical values described in the IZA Zeolite Structure Database 2017 Edition (http: / / www.iza-structure.org / databases / ) may be used.
[0042] Framework density: 16.0T / 1000Å 3 Larger, 17.0T / 1000Å 3 Examples of the following zeolites include zeolites of the ERI, LTL, LTN, MOZ, OFF, SAT, SSF and -WEN structure types. Framework density: 15.0T / 1000Å 3 Larger, 16.0T / 1000Å 3 Examples of the following zeolites include zeolites of the AEI, AFT, AFV, AFX, AVL, EAB, GME, LEV, MWW and SFW type structures. Framework density: 14.0T / 1000Å 3Larger, 15.0T / 1000Å 3 Examples of zeolites that may be mentioned include zeolites of the CHA, KFI, SAS and SAV structure types. Framework density: 14.0T / 1000Å 3 Examples of zeolites falling within the following ranges include zeolites of EMT, FAU, JSR, SBS, SBT, and TSC type structures.
[0043] (Silica / Alumina Molar Ratio (SAR) of Zeolite) The silica / alumina molar ratio (sometimes referred to as "SAR", "Si / Al2 molar ratio", or "Si / Al2 ratio") of the zeolite according to the present invention is not particularly limited as long as the effects of the present invention are not impaired. The SAR (Si / Al2 ratio) of the zeolite is preferably high in order to increase the moisture resistance of the resin composite material described below and to facilitate control of the amount of counter cations. Thus, the SAR (Si / Al2 ratio) of the zeolite is usually 2 or more, preferably 3 or more, more preferably 3.5 or more, even more preferably 4 or more, particularly preferably 4.5 or more, and most preferably 5 or more. On the other hand, the SAR (Si / Al2 ratio) of zeolite is preferably low in terms of easy and inexpensive production. Therefore, the SAR (Si / Al2 ratio) of zeolite is usually 2000 or less, preferably 1000 or less, more preferably 500 or less, and further preferably 100 or less. When the Si / Al2 ratio is within the above range, the amount of counter cations is easily controlled, and the production cost of zeolite is also low.
[0044] (Zeolite counter cation) The counter cation of the spherical zeolite to be produced in the present invention is not particularly limited as long as the effect of the present invention is not impaired. The counter cation of the zeolite is usually a proton, an alkali metal ion, or an alkaline earth metal ion. Preferably, it is a proton or an alkali metal ion, more preferably, it is a proton, a Li ion, a Na ion, or a K ion. In the case of an alkali metal ion or an alkaline earth metal ion, the smaller the size, the more likely the zeolite is to exhibit an average thermal expansion coefficient of less than 0 ppm / K, so this is preferable. Among these, the counter cation of the zeolite is preferably a proton, since this makes it easier to reduce the average thermal expansion coefficient of the resin composite. That is, the zeolite is preferably a proton type or an alkali metal type, more preferably a proton type, a Li type, a Na type, or a K type.
[0045] (Zeolite crystallinity) The crystallinity of the zeolite to be produced in the present invention is not particularly limited as long as the effect of the present invention is not impaired. The reason is that it is assumed that the Composite Building Unit (CBU) is a factor that has a greater influence on the average thermal expansion coefficient of the epoxy resin composite than the structure specified by the IZA code. The crystallinity of the zeolite can be calculated by comparing a certain X-ray diffraction peak determined by an X-ray diffractometer (e.g., BRUKER's tabletop X-ray diffractometer D2PHASER) with the X-ray diffraction peak of the reference zeolite. A specific calculation example is the crystallinity of LTA-type zeolite in Scientific Reports 2016, 6, Article number: 29210.
[0046] The method for producing spherical zeolite of the present invention includes a mixing step, an aging step, and a hydrothermal synthesis step. Each step will be described in detail below. In the production of zeolite, in addition to the above-mentioned components, components such as an acid component for accelerating the reaction and a metal stabilizer such as polyamine may be added at any step as necessary.
[0047] <Mixing process> More specifically, this is a step of preparing a synthesis raw material gel by mixing the above-mentioned silicon atom source, aluminum atom source, surfactant, water, an organic structure directing agent added as necessary, an alkali metal atom source, and seed crystal zeolite. When preparing the synthesis raw material gel, the order of addition of each raw material is not particularly limited, but from the viewpoint of easy control of viscosity change during mixing, the silicon atom raw material, aluminum atom raw material, surfactant, and alkali metal atom raw material are added to water and dissolved or dispersed. An organic structure directing agent is added as necessary, but it may be blended in the synthesis raw material gel from the beginning, or it may be added after the aging process described below and immediately before hydrothermal synthesis.
[0048] (Mixed condition) The mixing conditions for preparing the synthesis raw material gel are not particularly limited, but from the viewpoint of purity and uniformity, long mixing times are preferable. On the other hand, from the viewpoint of production efficiency, short mixing times are preferable. Therefore, the mixing time is preferably 30 s or more, and particularly preferably 60 s or more. On the other hand, 7200 s or less is preferable, 1800 s or less is more preferable, and 600 s or less is particularly preferable. Mixing with stirring is preferred from the viewpoint of facilitating the preparation of a uniform synthesis raw material gel.
[0049] <Aging process> The raw material composition obtained as described above may be hydrothermally synthesized immediately after preparation, but in order to obtain a zeolite with higher crystallinity, it is preferable to age the raw material for a certain period of time under a predetermined temperature condition. In particular, when the reaction is scaled up, it is preferable to age the raw material while stirring it for a certain period of time, since this improves the stirrability and makes the raw material more uniform. The temperature for aging is usually 100°C or less, preferably 95°C or less, more preferably 90°C or less, and although there is no particular limit to the lower limit, the temperature for aging is usually 0°C or more, preferably 10°C or more. The aging temperature may be constant during aging, or may be changed stepwise or continuously. The aging time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and on the other hand, is usually 30 days or less, preferably 10 days or less, and more preferably 4 days or less.
[0050] <Hydrothermal synthesis process> Next, the obtained raw material composition is subjected to hydrothermal synthesis. Hydrothermal synthesis is usually carried out by placing the raw material composition prepared as described above or an aqueous gel obtained by maturing the raw material composition in a pressure-resistant container, and maintaining the mixture at a predetermined temperature under self-generated pressure or under gas pressure to an extent that does not inhibit crystallization, while stirring, rotating or rocking the container, or leaving it stationary. In order to increase the reaction rate, the reaction temperature during hydrothermal synthesis is preferably 120°C or higher, more preferably 130°C or higher, even more preferably 140°C or higher, and particularly preferably 150°C or higher. On the other hand, it is usually 230°C or lower, preferably 220°C or lower, more preferably 200°C or lower, and even more preferably 190°C or lower. The reaction time is not particularly limited, but is usually 2 hours or more, preferably 3 hours or more, more preferably 5 hours or more, and on the other hand, it is usually 30 days or less, preferably 10 days or less, more preferably 7 days or less, and even more preferably 5 days or less. The reaction temperature may be constant during the reaction, or may be changed stepwise or continuously. The reason why the zeolite production method according to the present invention can produce particularly preferable zeolites is believed to be that the surfactant is adsorbed onto the surface of the growing zeolite crystals, causing the zeolite to grow while creating a state close to a spherical micelle structure.
[0051] <Drying process> After the hydrothermal synthesis, the zeolite is separated from the composition after the hydrothermal synthesis (hydrothermal synthesis reaction liquid). The method of separation is not particularly limited, but it is usually separated by washing with water, filtration, decantation, direct drying, etc. Even if it is separated by filtration or decantation, it is usually dried after that. Drying conditions are not particularly limited, and for example, the drying temperature is preferably 50° C. or higher and 200° C. or lower, and more preferably 70° C. or higher and 150° C. or lower. The drying atmosphere is not particularly limited, and the drying may be performed in air or in an inert atmosphere such as nitrogen or argon.
[0052] <Firing process> The dried zeolite is subjected to calcination or the like in order to remove the structure-directing agent and the like used during the production. The calcination temperature is usually preferably 300° C. to 1000° C. Calcination at 300° C. or higher can remove the organic structure directing agent, while calcination at 1000° C. or lower does not impair the physical properties of the zeolite. From the above viewpoints, the calcination temperature is preferably 400° C. or higher, more preferably 450° C. or higher, and even more preferably 500° C. or higher, and is preferably 900° C. or lower, more preferably 800° C. or lower, and even more preferably 700° C. or lower. The atmosphere for the firing is not particularly limited, and the firing may be performed in air or in an inert atmosphere such as nitrogen or argon. The calcination method is not particularly limited, and a muffle furnace, a kiln, a fluidized calcination furnace, etc. can be used, but the calcination method using the gas is preferable. The gas flow rate is not particularly limited, but the amount of gas flow per 1 g of powder is preferably in the range of 0.1 ml / min to 100 ml / min, and calcination is preferably performed under a gas flow of 5 ml / min to 20 ml / min.
[0053] <Resin composition> The zeolite produced by the production method of the present invention is a spherical zeolite with an extremely low average thermal expansion coefficient. Therefore, a resin composition comprising the spherical zeolite produced by the present invention (hereinafter referred to as "the zeolite according to the present invention") and a resin can constitute a composite material capable of suppressing thermal expansion. The content of the zeolite according to the present invention is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and especially preferably 50% by mass or more, based on the total amount of the resin composition, from the viewpoint of suppressing the increase in viscosity and lowering the thermal expansion coefficient. On the other hand, it is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 75% by mass or less, and particularly preferably 70% by mass or less. Furthermore, when a resin composition contains a filler other than the zeolite of the present invention, the content of the zeolite of the present invention in the total filler is preferably 10 mass % or more, more preferably 30 mass % or more, even more preferably 50 mass % or more, even more preferably 70 mass % or more, and most preferably 90 mass % or more, because this reduces the increase in viscosity during resin kneading and makes it easy to reduce the thermal expansion coefficient of the cured product.
[0054] (resin) The resin used in the resin composition is not particularly limited as long as it can achieve the effects of the present invention, but from the viewpoint of more easily achieving the effects of the composite material, it is preferably at least one type selected from the group consisting of epoxy resins and polyimide resins. In particular, when the resin composition is used as a sealant such as an underfill agent, epoxy resins are preferred. The amount of the resin contained in the resin composition according to the present invention is preferably 5% by mass or more, more preferably 10% by mass or more, based on the total amount of the composition, from the viewpoint of maintaining excellent physical properties of the resin and heat resistance (resistance to thermal expansion) of the cured resin composition, while being preferably 50% by mass or less, more preferably 25% by mass or less, and particularly preferably 15% by mass or less.
[0055] <<Epoxy resin>> As the epoxy resin used in the resin composition according to the present invention, it is preferable to use an epoxy compound having an aromatic ring such as a bisphenol A type skeleton, a bisphenol F type skeleton, or a biphenyl skeleton, since the thermal expansion coefficient of the epoxy resin composite material obtained by curing the liquid composition is likely to be low. Specifically, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, biphenyl type epoxy resin, naphthalene ring-containing epoxy resin, epoxy resin having a dicyclopentadiene skeleton, phenol novolac type resin, cresol novolac type epoxy resin, triphenylmethane type epoxy resin, aminophenol type epoxy resin, aliphatic epoxy resin, copolymer epoxy resin of aliphatic epoxy resin and aromatic epoxy resin, etc. are exemplified, among which bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, biphenyl type epoxy resin, and naphthalene ring-containing epoxy resin are preferred, and more preferably bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene ring-containing epoxy resin, aminophenol type epoxy resin, and biphenyl type epoxy resin are used.
[0056] It is preferable to use a polyfunctional epoxy resin because the glass transition temperature of the epoxy resin composite material obtained by thermally curing the liquid composition is likely to be high. As the polyfunctional epoxy resin, various phenols such as phenol novolac resin, cresol novolac resin, bisphenol A novolac resin, dicyclopentadiene phenol resin, phenol aralkyl resin, naphthol novolac resin, biphenyl novolac resin, terpene phenol resin, heavy oil modified phenol resin, and various phenols such as polyhydric phenol resins obtained by condensation reaction of various phenols with various aldehydes such as hydroxybenzaldehyde, crotonaldehyde, glyoxal, and glycidyl ether type polyfunctional epoxy resins such as epoxy resins produced from epihalohydrin and various phenolic compounds are preferable.
[0057] From the viewpoint of fluidity, the epoxy resin used in the present invention preferably has a viscosity of 5 Pa·s or less at 23°C, and more preferably 0.1 to 3 Pa·s. The method for measuring the viscosity of epoxy resins is specified in JIS K7233 (1986), and a single cylinder rotational viscometer method is suitable. The viscosity of the epoxy resin used in the present invention at 23°C may be measured using a B-type rotational viscometer ("LVDV-1 Pri", Brookfield, spindle: S62), which is one of the single cylinder rotational viscometer methods.
[0058] From the viewpoint of viscosity control, the epoxy resin preferably has an epoxy equivalent of 50 g / eq or more and 500 g / eq or less, more preferably 90 g / eq or more and 150 g / eq or less. The epoxy equivalent is preferably high in terms of excellent heat resistance. On the other hand, it is preferably low in terms of improving the filling property of the liquid composition and increasing the bonding property by filling, by lowering the melting point of the epoxy resin and lowering the viscosity. The epoxy resin may be used alone or in any combination and ratio of two or more kinds. When the resin is mixed, the epoxy equivalent is the equivalent weight of the mixture.
[0059] The content of the epoxy resin in the liquid composition of the present invention is preferably low in that the content of inorganic fillers and the like is relatively high and the thermal expansion coefficient is easily reduced. On the other hand, it is preferable that the content is high in that the excellent physical properties of the epoxy resin are easily maintained. Specifically, the content is preferably 5% by mass or more, more preferably 10% by mass or more, based on the total amount of the composition. On the other hand, it is preferably 50% by mass or less, more preferably 25% by mass or less, and particularly preferably 15% by mass or less.
[0060] (hardening agent) The liquid composition of the present invention preferably further contains a curing agent. The curing agent is a substance that contributes to the crosslinking reaction between crosslinking groups of the epoxy resin. The curing agent is not particularly limited, and can be generally known as an epoxy resin curing agent. For example, phenol-based curing agents, amine-based curing agents such as aliphatic amines, polyetheramines, alicyclic amines, and aromatic amines, acid anhydride-based curing agents, amide-based curing agents, tertiary amines, imidazole and its derivatives, organic phosphines, phosphonium salts, tetraphenylboron salts, organic acid dihydrazides, halogenated boron amine complexes, polymercaptan-based curing agents, isocyanate-based curing agents, blocked isocyanate-based curing agents, and dicyandiamine compounds can be mentioned. From the viewpoint of imparting fluidity and fast curing, acid anhydride-based curing agents are preferred as the curing agent.
[0061] When the liquid composition of the present invention contains a curing agent, the content of the curing agent is preferably in the range of 0.8 to 2.0, more preferably 0.8 to 1.5, in terms of the equivalent ratio of the epoxy groups in the epoxy resin to the functional groups in the curing agent (functional groups in the curing agent / epoxy groups in the epoxy resin), in the case of a phenol-based curing agent, an amine-based curing agent, or an acid anhydride-based curing agent, since influences due to residual unreacted epoxy groups or functional groups of the curing agent are unlikely to occur.
[0062] When the curing agent is an amide curing agent, a tertiary amine, imidazole and its derivatives, organic phosphines, phosphonium salts, tetraphenyl boron salts, organic acid dihydrazides, boron halide amine complexes, polymercaptan curing agents, isocyanate curing agents, blocked isocyanate curing agents, etc., it is preferably used in an amount of 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the epoxy resin, while it is preferably used in an amount of 20 parts by mass or less, more preferably 10 parts by mass or less. In the case of a dicyandiamine compound, it is preferably used in an amount of 0.1 part by mass or more, more preferably 0.5 part by mass or more, relative to 100 parts by mass of the epoxy resin, while it is preferably used in an amount of 10 parts by mass or less, more preferably 6 parts by mass or less.
[0063] (Viscosity of liquid composition) The liquid composition is a composition that has fluidity at room temperature (23°C). The viscosity of the resin composition of the present invention is preferably low in terms of ease of filling the composition even in a narrow space. On the other hand, it is preferable that the viscosity is high in terms of preventing dripping during filling of the composition. The viscosity of the liquid composition at 23°C is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, even more preferably 5 Pa·s or more, and particularly preferably 10 Pa·s or more. On the other hand, it is preferably 250 Pa·s or less, more preferably 200 Pa·s or less, even more preferably 150 Pa·s or less, particularly preferably 60 Pa·s or less, and especially preferably 30 Pa·s or less. The viscosity at 23°C is most preferably 1 Pa·s or more and 30 Pa·s or less. The viscosity of the liquid composition can be measured in the same manner as the viscosity measurement method for epoxy resins described above. The viscosity of the liquid composition used in the present invention at 23°C may be measured using a B-type rotational viscometer, which is one of the single cylinder rotational viscometer methods. For the B-type rotational viscometer, for example, the one described in the Examples may be used.
[0064] (Average thermal expansion coefficient) The average coefficient of thermal expansion (CTE1) of the liquid composition according to the present invention when cured is preferably low so that the epoxy resin composite is less likely to deform due to the surrounding temperature environment or heat generation. On the other hand, it is preferable that the average coefficient of thermal expansion is close to that of the surrounding members so that damage due to the difference in average thermal expansion with the surrounding members is less likely to occur. Therefore, when the liquid composition is used as an underfill material or the like in the manufacture of semiconductor devices, it is preferable that the average coefficient of thermal expansion is close to that of the semiconductor substrate (for example, 3 to 4 ppm / K). From the above viewpoints, the liquid composition according to the present invention, when cured, preferably has an average coefficient of thermal expansion (CTE1) of 0 ppm / K or more, more preferably 2 ppm / K or more, even more preferably 4 ppm / K or more, and particularly preferably 10 ppm / K or more, while it is preferably 200 ppm / K or less, more preferably 100 ppm / K or less, and particularly preferably 30 ppm / K or less.
[0065] The average thermal expansion coefficient of the cured product obtained by curing the liquid composition and the glass transition temperature (Tg) described later can be measured by measuring the average thermal expansion coefficient of the epoxy resin composite (cured product) obtained by curing the liquid composition to a gel fraction of 80% or more. The average thermal expansion coefficient (CTE1) is determined from the slope of the tangent line of the temperature change in the amount of change in the length of a sample measured at 25 to 100°C using a compression method based on thermomechanical analysis in accordance with JIS K7197 (2012).
[0066] (glass transition temperature) The glass transition temperature (Tg) of the epoxy resin composite material obtained by curing the liquid composition according to the present invention is not particularly limited. For example, when the underfill material has a high Tg, the part sealed with the underfill material is considered to be preferable because it has high bump protection at high temperatures and excellent thermal cycle resistance (see, for example, JP 2017-110146 A). From such a viewpoint, the glass transition temperature (Tg) of the cured product of the liquid composition according to the present invention when cured is preferably 50° C. or higher, more preferably 80° C. or higher. Furthermore, since warping at room temperature (23° C.) tends to be less likely to occur when the glass transition temperature is 150° C. or lower, the glass transition temperature (Tg) is preferably 50 to 150° C., and more preferably 80 to 150° C. The glass transition temperature (Tg) can be measured by a thermomechanical analyzer (TMA).
[0067] (Method of producing liquid composition) The liquid composition according to the present invention can usually be obtained by mixing and kneading the epoxy resin, the zeolite according to the present invention, and the curing agent, dispersant, reactive diluent, and other additive components used as necessary using a vacuum mixer, mixing roll, planetary mixer, etc., and degassing as necessary. The order of mixing these components is arbitrary as long as there are no particular problems such as the occurrence of reactions or precipitation, and any two or more of the constituent components may be mixed in advance and then the remaining components may be mixed, or all of the components may be mixed at once.
[0068] The liquid composition of the present invention is preferably used as a liquid sealant, and in this case, the epoxy resin composite material formed by curing the liquid composition preferably serves as a sealant. The liquid sealant may be used as a sealant that fills gaps formed in components and then hardens to fill the gaps. In addition, the liquid sealant may be used as a sealant for filling gaps between components by, for example, applying the liquid sealant onto various components, overlaying another component on the liquid sealant, and then appropriately curing the liquid sealant. In this case, the liquid sealant may be appropriately cured to a B-stage before overlaying the other component. Among these, the liquid composition of the present invention is preferably used for filling a gap and curing it. That is, it is preferable to produce a sealant by filling a gap with the liquid composition of the present invention and then curing it. The liquid composition of the present invention has a low viscosity, and can be filled into even a narrow gap without generating voids.
[0069] The liquid composition of the present invention is preferably used as a liquid sealant, and particularly preferably used as an underfill material. The underfill material is preferably used in the manufacture of electric devices, particularly semiconductor devices, and is preferably used to fill gaps formed between a substrate and a semiconductor chip, between substrates, between semiconductor chips, etc. The substrate may be a known substrate, and may be a substrate made of an organic material such as an epoxy resin substrate or a phenol resin substrate. The semiconductor chip may be formed from a semiconductor substrate such as a silicon substrate. The liquid composition of the present invention has a low coefficient of thermal expansion when cured, and when used as an underfill material, the difference in thermal expansion coefficient between the composition and semiconductor substrates and the like is reduced, thereby improving thermal cycle resistance and the like.
[0070] The underfill material is preferably used as a sealant that fills the gap between the substrate and the semiconductor chip in a laminate in which the semiconductor chip is mounted on the substrate, and then hardens by heating to seal the gap between the substrate and the chip. In this case, the semiconductor chip may be bonded to the surface of the substrate on which the wiring pattern is formed via bumps by, for example, reflow before the underfill material is filled.
[0071] The underfill material may be used in the manufacture of semiconductor devices by the pre-apply method. Specifically, on the surface of a semiconductor chip on which a plurality of bumps are formed, the underfill material is filled between the plurality of bumps to form an underfill layer. Here, the filled underfill material may be B-staged as necessary. Thereafter, the semiconductor chip on which the underfill layer is formed may be placed on the surface of the substrate with the surface on which the underfill layer is formed facing the substrate. Next, the underfill layer is hardened by heating and pressing, etc. to become an encapsulant, and the semiconductor chip may be bonded to the surface of the substrate on which the wiring pattern is formed via the bumps.
[0072] In the pre-apply method, an underfill material may be applied to the surface of a substrate on which a wiring pattern is formed to form an underfill layer. Here, the applied underfill layer may be B-staged as necessary. Then, the semiconductor chip on which the bumps are formed may be placed on the substrate on which the underfill layer is formed, with the surface on which the bumps are formed facing the surface of the substrate on which the underfill layer is formed. Then, the underfill layer is hardened by heating and pressing to become an encapsulant, and the semiconductor chip may be bonded to the surface of the substrate on which the wiring pattern is formed via the bumps.
[0073] In the above description, the underfill material is used as a sealant to fill the gap between the substrate and the semiconductor chip, but the use of the underfill material is not particularly limited, and the underfill material may be used to fill the gap between semiconductor chips, or as a sealant to fill the gap between substrates, etc. Furthermore, the substrate is not limited to a substrate made of an organic material, and may be a semiconductor substrate, etc. EXAMPLES
[0074] The production method of the present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited in any way. The evaluations and measurements in the examples were carried out by the methods shown below.
[0075] (Evaluation method) (1) XRD The powders obtained in the examples and comparative examples were packed into glass cells and measured using an X-ray diffraction device "D2PHASER" manufactured by BRUKER, to identify the phases.
[0076] (2) XRF Using a fluorescent X-ray analyzer "Supermini200" manufactured by Rigaku Corporation, the powders obtained in the examples and comparative examples were covered with a PP film and subjected to measurement to obtain the SiO2 / Al2O3 ratio.
[0077] (3) SEM The powders obtained in the examples and comparative examples were dispersed in ethanol and dropped onto a measurement stage to prepare measurement samples. Measurements were performed using a scanning electron microscope "JSM-6701F" manufactured by JEOL Ltd., and 419 particles were observed in Example 1 and 304 particles in Comparative Example 1 under conditions of an acceleration voltage of 10.0 kV and a magnification of 2000 times.
[0078] (4) Circularity The projected area and perimeter of each particle were calculated using the image processing software "ImageJ" from the SEM images. Then, a histogram of the circularity of each particle was created, and the percentage of particles with a circularity of 0.8 or more was calculated.
[0079] (5) Viscosity of the liquid composition The viscosity of the liquid composition at 23°C was measured using a B-type rotational viscometer. When the viscosity was 0.1 to 100 Pa·s, an "LVDV-1 Pri" manufactured by Brookfield, with spindles S64 and S63 was used as the B-type rotational viscometer, and when the viscosity exceeded 100 Pa·s, an "HBDV-E" manufactured by Brookfield, with spindle S-07 was used. The value measured at 20 rpm was used as the representative viscosity value for each sample.
[0080] [Example 1] <Preparation of gel before hydrothermal synthesis process> To 4.3 g of water, 13 g of a 20% aqueous solution of N,N,N-trimethyl-1-adamantaammonium hydroxide (manufactured by Seichem) was added as an organic structure directing agent, and 0.24 g of sodium oleate (manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) and 0.19 g of amorphous Al(OH)3 (Al2O3, 54 mass%, manufactured by Kyowa Chemical Industry Co., Ltd.) were added as surfactants. The mixture was stirred at 300 rpm at 25°C for 30 minutes, after which 6.0 g of Snowtex N-40 (silica concentration: 40 mass%, manufactured by Nissan Chemical Industries Co., Ltd.) was added and the mixture was stirred at 300 rpm at 25°C for 1 hour to obtain a pre-hydrothermal synthesis gel. The molar composition ratio of the gel before hydrothermal synthesis is shown below. SiO2: 0.025Al2O3: 25H2O: 0.3Structure directing agent: 0.02Surfactant
[0081] <Hydrothermal synthesis of zeolite> The pre-hydrothermal synthesis gel prepared by the above method was placed in a pressure-resistant container and hydrothermal synthesis was carried out for 48 hours while stirring at 150°C. After the hydrothermal synthesis reaction, the reaction solution was cooled and the generated crystals were collected by filtration. The collected crystals were dried at 100°C for 12 hours to obtain Powder 1. When the XRD of the obtained Powder 1 was measured, it was confirmed to be a CHA-type zeolite. The XRD chart of this Powder 1 is shown in Figure 1. The yield of the obtained CHA-type zeolite was 80%, and the SiO2 / Al2O3 ratio was 32 by XRF analysis.
[0082] <Caking zeolite> In order to remove the organic matter in the zeolite, the synthesized zeolite powder (powder 1) was calcined in an air stream at 600° C. for 6 hours to obtain the target zeolite powder from which the organic matter had been removed. The physical properties of the zeolite were evaluated by the methods described above, and the evaluation results are shown in Table 1.
[0083] [Comparative Example 1] A zeolite was produced in the same manner as in Example 1, except that no surfactant was used. The results of evaluation performed in the same manner as in Example 1 are shown in Table 1.
[0084] [Table 1]
[0085] It can be seen that the zeolite produced by the production method of Example 1 is spherical and highly circular because a surfactant is used in the production process. On the other hand, in Comparative Example 1, no surfactant is used, and therefore no spherical zeolite with high circularity is obtained. Since the zeolite produced in Example 1 is spherical, it is expected that the resin kneading viscosity is small when mixed with a resin to form a resin composition, and that the thermal expansion coefficient is small. Therefore, when used as an underfill agent, a liquid sealant with good thermal cycle resistance and good injectability can be obtained. [Industrial Applicability]
[0086] According to the manufacturing method of the present invention, spherical zeolite can be efficiently manufactured, and a resin composition using the zeolite has a small thermal expansion coefficient and high injectability, and is therefore useful as an underfill agent. Therefore, the manufacturing method of spherical zeolite of the present invention is a technology of high industrial value.
Claims
1. A method for producing spherical zeolite having d6r as CBU, characterized in that a surfactant is contained in a raw material gel for zeolite synthesis.
2. The method for producing spherical zeolite according to claim 1, wherein the zeolite has a structure having an oxygen ring of 8 or less members.
3. 2. The method for producing spherical zeolite according to claim 1, wherein the ratio of the number of particles of the zeolite having a circularity of 0.8 or more is 90% or more.
4. The method for producing spherical zeolite according to claim 1, wherein the zeolite is a CHA type zeolite.
5. The method for producing spherical zeolite according to claim 1, wherein the surfactant is an ionic surfactant.
6. The method for producing spherical zeolite according to claim 5, wherein the ionic surfactant is an anionic surfactant or a cationic surfactant.
7. 2. The method for producing spherical zeolite according to claim 1, wherein the synthesis raw material gel contains a silicon atom raw material, an aluminum atom raw material, a surfactant, and water, and further comprises a step of hydrothermally synthesizing the synthesis raw material gel.
8. The method for producing spherical zeolite according to claim 7, wherein the synthesis raw material gel further contains an organic structure directing agent.
9. The method for producing spherical zeolite according to claim 7, further comprising a drying step and a calcination step.
Citation Information
Patent Citations
Under fill material for flip chip type semiconductor device, the flip chip type semiconductor device using the same and method for producing the device
JP2007056070A
Cited By
Bottle
USD1131224S